Microclimatic and photosynthetic characteristics in arecanut and cardamom mixed cropping system - Yadukumar, Rajendra Hegde, M M Hosman, V S Korikanthimath, S J Ankegowda, N (Journal of Spices and Aromatic Crops, 2000)
The microclimatic and photosynthetic characteristics of arecanut (Areca catechu) and cardamom (Elettaria cardamomum) mixed cropping system were studied at Sirsi (Kamataka, India). Arecanut canopy received higher amount of light and also photosynthetically active radiation. Arecanut also recorded higher photosynthetic rate, transpiration rate, stomatal conductance, intercellular CO2 concentration, carboxylation efficiency and water use efficiency at gas exchange level.